Photocatalytic and hydrophobic activity of cement-based materials from benzyl-terminated-TiO2 spheres with core-shell structures. (1st September 2017) - Wang, Dan; Hou, Pengkun; Zhang, Lina; Yang, Ping; Cheng, Xin
Graphical abstract: Hydrophobic TiO2 samples were designed by employing organic small molecule for coating the cement-based materials, which were obtained via a solvothermal process. The color fading rates of cement paste coated TiO2 are more than 30% at 1 h. After irradiating for 15 h, the color fading rates of cement paste coated TiO2 are more than 80%, which are about 3.6 times than untreated cement paste. Highlights: Hydrophobic TiO2 samples were designed by employing organic small molecule for coating the cement-based materials. Benzoic acid not only has surface binding forming with TiO 2, but also influences the formation of core-shell structure. The cement paste coated TiO2 has high photocatalytic property, which is about 3.6 times than untreated cement paste. The cement paste coated TiO2 has hydrophobic property. Abstract: The application of the photocatalytic technology on the building materials could be very necessary, especially for the surface. Hydrophobic TiO2 samples were designed by employing organic small molecule for coating the cement-based materials, which were obtained via a solvothermal process. The core-shell structure was prepared by using benzoic acid as a surfactant. The surface binding forming for benzoic acid supported on TiO2 surface has been studied by the Fourier transform infrared spectroscopy. Benzoic acid has surface binding forming with TiO2, which leads to the hydrophobicity of TiO2 . Meanwhile, benzoic acid acts as a catalyst to promote the hydrolysis of Ti precursor and influences the formation of core-shell structure. The hydrophobic and photocatalytic properties of cement-based materials coated with TiO2 have been investigated. The water contact angle of cement paste coated TiO2 can reach 90.5°. The color fading rates of cement paste coated TiO2 are more than 30% at 1 h. After irradiating for 15 h, the color fading rates of cement paste coated TiO2 are more than 80%, which are about 3.6 times than untreated cement paste.